Manusia dan Sunnah Kemanusiaan - Ahmad Rifqi Muchtar (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2007)
This writing reexamines the position of humans in contemporary life. Humans, from ancient times until now, remain a significant enigma and a profound mystery. They are earthly beings, yet distinct from other earthly creatures in various aspects. They possess sacred values, yet cannot be equated with creatures that have been sanctified. This is because humans are a combination of both, filled with various potentials. The language of the Qur'an refers to them as 'Ahsan Taqwim' – the best of creation.